Efektivitas Kegiatan Outbound Fun Estafet untuk Meningkatkan Perkembangan Sosial Anak di Taman Kanak–Kanak Al-Jannah Tarusan Kabupaten Pesisir Selatan - Rolla Afriza Yeni; Prima Aulia (SELING: Jurnal Program Studi PGRA, 2019)
The purpose of this study was determine the effectiveness of relay outbound fun activities on improving social development of children in aljannah tarusan kindergarten kabupaten pesisir selatan. In this study quantitative research in the form of quasy experiments was used. The result showed that according ti the analysis of indpendent data from the sample t-test using SPSS for windows 23, previously the normality and hmogenity test were carried out, and also with the N-Gain score test. The result obtained sig (2-tailed) 0,012 <0,05 means that there is a significant (significant) difference in effectiveness between the treatment given by the teacher and the treatmeant of relay outbound fun activities to improve children’s social development. Based on the analysis of the result of the hypothesis test and the effect test, it was concluded that the effective relay outbound activity was effective to enhance the social development of children at al-jannah Tarusan Kindergarten, Kabupaten Pesisir Selatan.